Magnetic resonance imaging in the diagnosis of HTLV-1-associated myelopathy - Carvalho, João Marcos; Ferraz, Sheila Nunes; Abraão Neto, José; Schnitman, Saul; Carvalho, Augusto M.; Carvalho, Edgar M. (Arquivos de Neuro-Psiquiatria, 2025)
The main neurologic manifestation of definitive human T-lymphotropic virus 1 (HTLV-1)-associated myelopathy (HAM) is spastic paraparesis, but it only occurs in 5% of the patients. In contrast, about 40% of HTLV-1-infected subjects present symptoms of urologic dysfunction, including nocturia, urgency, and incontinence, which may progress to an inability to void urine. As these patients do not present motor dysfunction, they are classified as probable HAM. Atrophy of the thoracic spinal cord (SC) is the main abnormality found on magnetic resonance image (MRI) scans of patients with definitive HAM, but damage to the SC has not been reported in patients with probable HAM.To determine if, through an evaluation of the metrics of conventional MRI, we can detect a decrease in the area of the SC in patients with probable HAM.Infection by HTLV-1 was herein diagnosed by a Western blot, and the MRI scan was performed using a 1.5-T scanner. Atrophy was considered when the SC area was less than 25% of the intrathecal area.We observed a progressive reduction in all segments of the SC area among HTLV-1 carriers, patients with probable and definitive HAM. Significantly, 48.3% of patients with probable HAM presented atrophy of the lumbar area.Using MRI metrics, the present study shows the atrophy of lumbar segments of the SC area in patients who present urinary symptoms associated with HTLV-1 but without motor dysfunction.
Keywords: Human T-lymphotropic Virus 1; Paraparesis, Tropical Spastic; Magnetic Resonance Imaging; Lower Urinary Tract Symptoms